Legal regulation of the circulation of pyrotechnic products in Ukraine and administrative responsibility for its violation (Law and Safety, 2022)
The paper examines the regulations governing the circulation of pyrotechnic articles in Ukraine. The content of the Technical Regulation of Pyrotechnics, which came into force in January 2022, is revealed. These regulations determine the classes of pyrotechnic articles, the legal regime of their free circulation, the responsibilities of economic entities and their identification, labeling of pyrotechnic articles, the procedure for establishing the conformity of pyrotechnic articles, technical requirements for the safety of pyrotechnic articles. It is emphasized that the Technical Regulations establish age restrictions on the sale or transfer of pyrotechnic articles to persons under the age of: 12 years (class F1), 16 years (class F2), 18 years (class F3).The peculiarities of transportation of pyrotechnic articles in accordance with the Law of Ukraine “On Transportation of Dangerous Goods” and orders of the Ministry of Internal Affairs of Ukraine governing the issuance and issuance of certificates of admission of vehicles for transportation of dangerous goods.The bases of administrative responsibility for violation of rules of trade and use of pyrotechnic products are defined. It is emphasized that it is characterized by insufficient clarity and gaps. In 2017, the order of the Ministry of Internal Affairs of Ukraine “On approval of the Provisional Rules of Circulation of Household Pyrotechnic Products in Ukraine” was revoked, as a result of which the normative grounds for bringing to administrative responsibility those who violated the rules of trade, storage and use of pyrotechnic products disappeared. It is proved that due to insufficient legal regulation, as well as low legal training of employees of the National Police and judges of general courts, during 2019–2021 many individuals were brought to administrative responsibility under Article 195-6 of the Code of Administrative Offenses of Ukraine without proper legal grounds. In addition, it was found that the lack of proper legal regulation and regulations of the Ministry of Internal Affairs of Ukraine on the legal regime of household pyrotechnic articles leads to the fact that the judiciary closes cases of administrative offenses under Article 195-6 of the Code of Administrative Offenses.The ways to improve the current legislation of Ukraine on the circulation of pyrotechnic articles in Ukraine, as well as to establish clear grounds for administrative liability for violations of the rules of manufacture, transportation, storage, trade, use of pyrotechnic articles and their sale to minors are highlighted in the article.
Keywords: pyrotechnic products; circulation of pyrotechnic products; administrative offense; administrative responsibility; Code of Ukraine on administrative offenses; administrative penalties; minors.